Galactic perturbations on the population of wide binary stars with exoplanets - Correa Otto, Jorge Alfredo (2017)
Aims. The aim of this work is to study the dynamical effects of the Galaxy on binary star systems with physical and orbital characteristics similar to those of the population of known wide binary stars with exoplanets. As secondary goal we analyse the possible consequences on the stability of a hypothetical planetary system orbiting one of the stellar components. Methods. We numerically reproduced the temporal evolution of a sample of 3 × 105 binary star systems disturbed by the Galactic potential and passing stars in an environment similar to the solar neighbourhood. Results. Our results show that the dynamical evolution of the population of wide binary stars with exoplanets in the solar neighbourhood is modelled by the process of disruption of binary star systems induced by the Galaxy. We found that this process depends mainly on the separation between both stars, whereas it is almost independent of the initial orbital configuration. Moreover, our calculations are in agreement with the results of previous works regarding the indirect influence of the Galaxy on the stability of planetary systems in wide binary stars. However, the effects on the planetary region show a dependence on the initial configuration of binary stars. Finally, we obtain an indirect test of the impulse approximation model for dynamical studies of binary star systems.